Heritability Analysis and Phenotypic Characterization of Spider Plant (Cleome gynandra L.) for Yield - Ann Kangai Munene; Felister Nzuve; Jane Ambuko; Damaris Odeny (Advances in Agriculture)
Knowledge on phenotypic diversity among existing spider plant accessions is a milestone in the improvement of spider plant, which is a highly nutritious indigenous vegetable in Kenya. A study involving agronomic and morphological characterization of 49 spider plant accessions assembled from East and South Africa was carried out at the University of Nairobi Field Station for two seasons in a randomized complete block design with three replications. Phenotypic data was collected on growth habit, flower, petiole, leaf and stem colour, petiole, leaf and stem hairiness, number of leaves per plant, plant height, number of primary branches, leaf length and width, single leaf area, and chlorophyll content according to FAO descriptors with modifications. Data was analyzed using both DARwin software V6 and Genstat Version 14. We observed significant differences among the traits implying great genetic variability among the evaluated spider plant accessions. The high genetic variation was further validated using the Unweighted Pair Group Method with Arithmetic mean (UPGMA) clustering method with stem and flower colour as key traits. The 49-spider plant accessions were clustered into 2 major groups, each consisting of Kenyan and South African accessions. Stepwise regression revealed that plant height had the most influence on yield in terms of number of leaves per plant. We also observed high heritability for several traits including days to flowering (91%), number of leaves per plant (99%), plant height (99%), number of primary branches (94%), chlorophyll content (94%), and single leaf area (87%). Our results reveal the high genetic variation between different spider plant accessions, especially from different regions of Africa that could be further exploited to improve productivity in the plant. The high heritability of most of the yield related traits is promising for improving yield in the crop through direct selection.